1982
DOI: 10.1002/bem.2250030202
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated development of spontaneous and benzopyrene‐induced skin cancer in mice exposed to 2450‐MHz microwave radiation

Abstract: (S.S., A.S., A.P., M.B., M.J., J.K. W.)C3H/HeA mice with high incidence of spontaneous breast cancer and Balb1c mice treated with 3,4-benzopyrene (BP) (by painting of the skin resulting in the development of skin cancer) were irradiated with 2,450-MHz microwaves (MW) in an anechoic chamber at 5 or 15 mW/cm2 (2 h daily, 6 sessions per week). C3WHeA mice were irradiated from the 6th week of life, up to the 12th month of life. Balb1c mice treated with BP were irradiated either prior to (over 1 or 3 months) or sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…Liddle et al [1994], on the other hand, found an effect on lifespan at 6.8 W/kg only and not at 2 W/kg. Szmigielski et al [1982] exposed mice for 2 h/day and stated that neither dose rate range (2-3 and 6-8 W/kg) caused an increase in rectal temperature, but this information does not agree with the experience of other investigators. Liddle et al [1994], for example, estimated a rectal temperature increase of about 0.8 8C in mice exposed individually at 6.8 W/kg for 1 h/day, one-half the exposure time used by Szmigielski et al No significant rise in body temperature of the mouse would be expected at the lower dose rate of 2 W/kg under the experimental conditions described by Liddle et al [1994], but this may not have been true for mice that could huddle together when exposed in groups of 10 per cage [Szmigielski et al, 1982].…”
Section: Survivalmentioning
confidence: 77%
See 4 more Smart Citations
“…Liddle et al [1994], on the other hand, found an effect on lifespan at 6.8 W/kg only and not at 2 W/kg. Szmigielski et al [1982] exposed mice for 2 h/day and stated that neither dose rate range (2-3 and 6-8 W/kg) caused an increase in rectal temperature, but this information does not agree with the experience of other investigators. Liddle et al [1994], for example, estimated a rectal temperature increase of about 0.8 8C in mice exposed individually at 6.8 W/kg for 1 h/day, one-half the exposure time used by Szmigielski et al No significant rise in body temperature of the mouse would be expected at the lower dose rate of 2 W/kg under the experimental conditions described by Liddle et al [1994], but this may not have been true for mice that could huddle together when exposed in groups of 10 per cage [Szmigielski et al, 1982].…”
Section: Survivalmentioning
confidence: 77%
“…Szmigielski et al [1982] exposed mice for 2 h/day and stated that neither dose rate range (2-3 and 6-8 W/kg) caused an increase in rectal temperature, but this information does not agree with the experience of other investigators. Liddle et al [1994], for example, estimated a rectal temperature increase of about 0.8 8C in mice exposed individually at 6.8 W/kg for 1 h/day, one-half the exposure time used by Szmigielski et al No significant rise in body temperature of the mouse would be expected at the lower dose rate of 2 W/kg under the experimental conditions described by Liddle et al [1994], but this may not have been true for mice that could huddle together when exposed in groups of 10 per cage [Szmigielski et al, 1982]. Concerns about temperature levels in exposed mice, uncertainty in dosimetry data due to exposure of 10 mice per cage, and effects at RF exposure levels that reportedly did not increase body temperature have contributed to the controversy surrounding the Szmigielski et al study since it was published over 20 years ago.…”
Section: Survivalmentioning
confidence: 77%
See 3 more Smart Citations